‘New Logistics’ of Russia’s Foreign Trade and Induced Problem of Identifying the Carrier’s Status - Andrei M. Golubchik; Egor V. Pak (RUDN Journal of Economics, 2024)
Formation of Russia’s ‘new logistics’ of foreign trade has logically led to new challenges. With longer routes and higher cost of transportation already being mitigated institutional hurdles such as carrier’s jurisdiction, limit of liability, and status have come to the front. When Western liner majors were in place these questions were more or less familiar to the majority of Russian foreign trade actors. In general carrier’s jurisdiction correlates with its place of registration. However, the situation has changed with logistics businesses floating into more friendly and convenient jurisdictions. For instance, all disputes with Danish MAERSK and Swiss MSC are to be resolved in English High Court of Justice in London. It is worth stressing that related information could be found on page 1 of the Bill of Lading in the ‘jurisdiction’ clause. Yet, after February 2022 with massive entrance of small and medium sea carriers from ‘friendly states’ onto the Russian market the range of jurisdiction applied has become wider. As of today, the most frequently met jurisdiction of carriers servicing Russia’s foreign trade is represented by Turkey, UAE, China, Hong Kong, Malaysia and Singapore. Thus, Russian foreign trade actors have faced a dare concerning the process of carrier’s identification: is it a factual carrier or a freight-forwarder who has become a carrier under the carriage contract? The answer though is not easy to reach. To sum it up, the authors highlight these failing points and neatly picture them using real cases from the field.